Near-Barrierless CO Oxidation Using Phosphotungstic Acid-Supported Single-Atom Catalysts - Wang, Kaijie; Li, Shiyu; Yang, Anqi; Chen, Dandan; Xu, Feng; Zhang, Li-Long; Zhang, Jian; Yang, Song (Inorganic chemistry, 2024)
Efficient CO oxidation at ambient or low temperatures is essential for environmental purification and selective CO oxidation in H2, yet achieving this remains a challenge with current methodologies. In this research, we extensively evaluated the catalytic performance of phosphotungstic acid (PTA)-supported 11 M1/PTA single-atom catalysts (SACs) using density functional theory calculations across both gas phase and 12 common solvents. The Rh1/PTA, Pd1/PTA, and Pt1/PTA systems exhibit moderate CO adsorption energies, facilitating the feasibility of oxygen vacancy formation. Remarkably, the Pd1/PTA and Pt1/PTA catalysts exhibited negligible energy barriers and demonstrated exceptionally high catalytic rates, with values reaching up to (1 × 1010)11, markedly exceeding the threshold for room temperature reactions, set at 6.55 × 108. This phenomenon is attributed to a transition from the high-energy barrier processes of oxygen dissociation in O2 and N–O bond dissociation in N2O to the more efficient dissociation of H2O2. Orbital analysis and charge variations at metal sites throughout the reaction process provide deeper insights into the role of the three metal catalytic sites in CO activation. Our findings not only reveal key aspects of SACs in facilitating CO oxidation at low temperatures but also provide valuable insights for future catalytic reaction mechanism studies and environmental applications.